HUBUNGAN PENGETAHUAN IBU HAMIL DAN DUKUNGAN KELUARGA DENGAN PERILAKU PENCEGAHAN ANEMIA DEFESIENSI BESI DI PUSKESMAS TANJUNG PINANG KOTA JAMBI - M Hidayat (Universitas Baiturrahim, 2017)
Background : Anemia disease occurs due to low hemoglobin content in the body during pregnancy. Anemia in pregnancy is a condition of the mother with hemoglobin levels below 11 gr%, especially in the first trimester and trirmester III. Based on data from jambi city health office, the number of incidence of anemia in pregnant women of Jambi in 2016 is highest in Tanjung Pinang Public Health Center as many as 924 cases. Method : This study was conducted to determine the relationship of knowledge of pregnant women and family support in the prevention of iron deficiency anemia. The research design used was quantitative with cross sectional approach. The population in this study amounted to 924 people. The sample in this study amounted to 35 by using accidental sampling technique. This study was conducted on September 16-22, 2016. The data obtained were univariat and bivariate analyzed by Chi-Square test. Result : There is a significant correlation between knowledge and behavior of pregnant mother in effort to prevent iron deficiency anemia at Tanjung Pinang Public Health Center of Jambi City in 2016, with chi square statistic test obtained p-value = 0,013 <0,05. There is a significant correlation between family support and behavioral effort of prevention of iron deficiency anemia at Puskesmas Tanjung Pinang Jambi City 2016, with chi square statistic test obtained p-value = 0,002 <0,05. It is expected that the Tanjung Pinang Public Health Center of Jambi City will improve the service quality for pregnant women who visit ANC and make health education program related to prevention problem of anemia for pregnant women and their families.